BASIC CONCEPTS AND APPROACHES TO IMPROVING PHYSICAL EDUCATION AMONG STUDENTS - Abbasov Bakhadir Asatillayevich (American Journals, 2022)
The analysis of modern concepts and approaches to the improvement of physical education of students is carried out, promising ways of transformation of the physical culture and sports environment are identified. It is proved that the organization of the physical culture and sports environment expands the field for humanitarian transformations of physical education of students, promotes diversification and personality-oriented orientation of physical education.
Keywords: physical education of students, concepts, approaches,, efficiency, improvement, humanitarization